Physical properties of safflower grains. Part II: Volumetric shrinkage - Elton A. S. Martins; André L. D. Goneli; Alexandre A. Gonçalves; Cesar P. Hartmann Filho; Jerusa Rech; Guilherme C. Oba (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Agricultural products usually have their size reduced during the drying process. The quantification of the reduction in the dimensions is important for the development and optimization of equipment for the post-harvest of the product. The aim of the present study was to evaluate the effect of the variation in the moisture content during drying on the volumetric shrinkage of safflower grains and their respective axes. Safflower grains were harvested with an initial moisture content of approximately 0.445 decimal d.b. (dry basis) and subjected to drying in an oven with forced air circulation at 40 °C, until the grains reached a final moisture content of 0.073 ± 0.008 decimal d.b. During drying, the contraction of the axes, unit volumetric shrinkage and volumetric shrinkage of the mass of safflower grains were determined at different moisture contents. Based on these results, it can be concluded that reducing the moisture content causes a reduction in the axes of safflower grains and, consequently, reductions in the unit volumetric shrinkage and volumetric shrinkage of the mass of approximately 16 and 13%, respectively, and both variables can be represented by the linear shrinkage model.